Measuring Connection to Nature—A Illustrated Extension of the Inclusion of Nature in Self Scale - Kleespies, Matthias Winfried; Braun, Tina; Dierkes, Paul Wilhelm; Wenzel, Volker (Sustainability, 2021)
The human-nature connection is an important factor that is frequently the subject of environmental education research and environmental psychology. Therefore, over the years, numerous measuring instruments have been established to quantitatively record a person’s connection to nature. However, there is no instrument specifically for children with cognitive limitations. For this reason, in this study, an established scale for connection to nature, the inclusion of nature in self scale (INS), was modified especially for the needs of this group. Study 1 investigated what students understand by the term “nature” in order to create an illustrated version of the INS. In study 2, the new instrument was tested on university students and compared with the original INS and the connectedness to nature scale (CNS). No significant differences between the original INS and the new developed scale were found (p = 0.247), from which it can be concluded that the illustrated INS (IINS) measures the connection to nature with similar accuracy as the original INS. In study 3, the instrument was tested together with other established nature connection instruments on the actual target group, students with disabilities. The correlation between the IINS, the CNS, and nature connectedness scale (NR) were in accordance with the expected literature values (rIINS-CNS = 0.570 & rIINS-NR = 0.605). The results of this study also prove effectiveness of the developed illustrated scale. This research thus provides a suitable measuring instrument for people with learning difficulties and can make a contribution to the investigation of human-nature connections and conservation education.